European demands for food quality and safety - Bulatsyk, Sofiya; Yavorska, Nadiya (Видавництво Львівської політехніки, 2017)
In this article was investigated regulations and other normative documents of the European Union concerning food quality and safety and was arranged EU demands regards to food safety. There were determined the basic business concerns of the domestic enterprises in the process of manufacturing and marketing food products
Keywords: quality; safety; foods; EU demands; regulations